Migration and informal insurance - Costas Meghir; Ahmed Mushfiq Mobarak; Corina Mommaerts; Melanie Morten (Yale University, Economic Growth Center, 2020)
Do new migration opportunities for rural households change the nature and extent of informal risk sharing? We experimentally document that randomly offering poor rural households subsidies to migrate leads to a 40% improvement in risk sharing in their villages. Our model of endogenous migration and risk sharing shows that risky and temporary migration opportunities can induce an improvement in risk sharing enabling profitable migration. Accounting for improved risk sharing, the migration experiment increased welfare by 12.9%. However, permanent declines in migration costs improve outside options for households and can lead to reductions in risk sharing. The short-run experimental results for migration subsidies can differ from the longer-run impacts of a policy that permanently subsidizes migration.
Older version: http://hdl.handle.net/10419/227646
Keywords: D12; D91; D52; O12; R23; 330; Informal Insurance; Migration; Bangladesh; RCT